The Role Of Profitability In Mediating Determinants Of Firm Value - Inrawan, Ady; Lie, Darwin (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the role of profitability in mediating the relationship between liquidity, leverage, and firm size on firm value. The data used in this study are secondary data obtained from the Indonesia Stock Exchange websites. The population comprises 71 companies listed in the LQ45 index for 2018-2022. The study sample includes 18 non-bank companies within the LQ45 index, selected through purposive sampling, yielding 90 observations over five years. Data analysis was conducted using panel data with EViews 13 software. Model selection was carried out through the Chow, Hausman, and Lagrange Multiplier tests. The study results show that liquidity does not affect profitability, while leverage negatively affects profitability, but company size positively affects profitability. Furthermore, leverage negatively affects firm value, liquidity, and company size do not affect firm value, but profitability positively affects firm value. Profitability cannot mediate the effect of liquidity and firm size on firm value, but profitability can mediate the effect of leverage on firm value. Theoretically, this research complements previous theories and serves as a reference for future studies. Practically, investors can utilize this information to exercise caution when assessing companies with high leverage levels but low profitability.